Association of Impaired Fasting Blood Glucose With Triple Coronary Artery Stenosis and Myocardial Infarction Among Patients With Coronary Artery Stenosis - Chen, Chang; Chen, Yequn; Xiao, Jiaxin; Zhang, Yanhong; Yang, Zhaorui; Yang, Peixuan; Lu, Nan; Yi, Kaihong; Chen, Xiaojun; Chen, Shaoxin; O'Gara MSc, Mary Clare; O'Meara, Michael; et al. (Frontiers in Cell and Developmental Biology, 2022)
Background: The association between impaired fasting glucose level (IFG) and coronary heart disease (CAD) remain controversial. In the present study, we sought to ascertain a relationship of IFG with the number of diseased coronary artery and occurrence of myocardial infarction, among CAD cases. Methods: We studied 1451 consecutive no-diabetic patients who underwent coronary angiography at the First Affiliated Hospital of Shantou University Medical College in Southern China. Demographic, biochemical, clinical and angiographic data were collected. Results: The prevalence of IFG was higher in patients with angiographically confirmed CAD than in subjects without angiographic evidence of CAD (28.2% versus 33.4%, P=0.034). Compared with CAD cases without IFG, CAD cases with IFG had a higher odds ratio (OR) of having triple-vessel disease as opposed to having single- or double-vessel disease [OR=1.53, 95% confidence interval (CI)=1.13-2.07]. Furthermore, the occurrence of MI was higher in CAD cases with IFG than in CAD cases without IFG (OR=1.73, 95% CI=1.27-2.36). Conclusions: There is an association between IFG and a predisposition to severe CAD indicated by triple vessel disease or myocardial infarction.